2007
DOI: 10.1055/s-2007-963303
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis intermedia im Kindesalter

Abstract: Round 10-12% of all children who present with signs of uveitis suffer from intermediate uveitis. Compared to uveitis anterior in children, the association of intermediate uveitis to a systemic disease is much more complicated. Most cases of uveitis intermedia are idiopathic and show the signs of a pars planitis. Post-infectious and immunological causes are difficult to detect. In cases of uveitis in children, it is necessary to know the specific symptoms of possible underlying systemic diseases. On this basis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
1
1
2
Order By: Relevance
“…IU affects patients in all age groups, from children to adults. 2,16 The mean age at disease onset of our patients was 19.4 years, younger than reported in other populations like Grajewski et al 17 Usually, the prevalence of females and males is similar as found in our study. 2 However, Paroli et al 18,19 and Silpa-Archa et al 20 found a slightly greater female 21 found a male predominance in patients with pars planitis.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…IU affects patients in all age groups, from children to adults. 2,16 The mean age at disease onset of our patients was 19.4 years, younger than reported in other populations like Grajewski et al 17 Usually, the prevalence of females and males is similar as found in our study. 2 However, Paroli et al 18,19 and Silpa-Archa et al 20 found a slightly greater female 21 found a male predominance in patients with pars planitis.…”
Section: Discussionsupporting
confidence: 83%
“…IU affects patients in all age groups, from children to adults. 2 , 16 The mean age at disease onset of our patients was 19.4 years, younger than reported in other populations like Grajewski et al 17 in Germany and Vidovic-Valentincic et al 7 in Slovenia where the average age at onset was 44 years and 31 years, respectively.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Im Gegensatz dazu verläuft die Uveitis intermedia im Kindesalter analog zum Erwachsenenalter in 80 % idiopathisch [3,4]. Sarkoidose, MS, chronisch entzündliche Darmerkrankungen sowie eine postinfektiöse Ursache müssen trotzdem ausgeschlossen werden, da die idiopathische Genese eine Ausschlussdiagnose darstellt [5]. Eine Uveitis posterior wird dagegen im Kindesalter meistens durch eine infektiöse Ursache ausgelöst, wobei hier an 1.…”
Section: äTiologie Der Uveitis Intermedia Und Posteriorunclassified
“…Stelle die Toxoplasmose-Retinochorioiditis zu nennen ist. Borrelien, Toxocara, Syphilis und Tbc sind deutlich seltener als Ursache zu finden [5].…”
Section: äTiologie Der Uveitis Intermedia Und Posteriorunclassified